Directional torsion and temperature discrimination based on a multicore fiber with a helical structure - Zhang, Hailiang (2019)
We propose and experimentally demonstrate a directional torsion sensor based on a Mach-Zehnder interferometer formed in a multicore fiber (MCF) with a ~570-μm-long helical structure (HS). The HS was fabricated into the MCF by simply pre-twisting and then heating with a CO2 laser splicing system. This device shows the capability of directional torsion measurement from −17.094 rad/m to 15.669 rad/m with the sensitivity of ~0.118 nm/(rad/m). Moreover, since the multiple interferences respond differently to torsion and temperature simultaneously, the temperature cross-sensitivity of the proposed sensor can be eliminated effectively. Besides, the sensor owns other merits such as easy fabrication and good mechanical robustness.